2018
DOI: 10.1002/ejic.201701440
|View full text |Cite
|
Sign up to set email alerts
|

SnO2Based Catalysts with Low‐Temperature Performance for Oxidative Coupling of Methane: Insight into the Promotional Effects of Alkali‐Metal Oxides

Abstract: To develop reactive catalysts for oxidative coupling of methane at low temperatures, different alkali-metal oxides are adopted in this study to modify the surface of SnO 2 . In comparison with the unmodified SnO 2 , the reaction performance of all of the modified catalysts can be significantly improved, among which lithium oxide shows the best promotional effects, and the optimal catalyst is achieved with a Sn/Li molar ratio of 5:5. With this catalyst, the highest C 2 product yield of 16 % is achieved at 750°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…As evidenced in Figure 10, the C 2 -C 3 yield obtained at 700 • C correlates well with the number of moderate basic sites present on the Ho 2 O 3 -based catalysts. This finding is in accordance with some previous reports that the surface basic sites with moderate strength are more favorable for the C 2 product formation in the OCM process [25,26,44,55,[57][58][59][60].…”
Section: Temperature-programmed Desorption (Tpd) Of O 2 and Cosupporting
confidence: 93%
“…As evidenced in Figure 10, the C 2 -C 3 yield obtained at 700 • C correlates well with the number of moderate basic sites present on the Ho 2 O 3 -based catalysts. This finding is in accordance with some previous reports that the surface basic sites with moderate strength are more favorable for the C 2 product formation in the OCM process [25,26,44,55,[57][58][59][60].…”
Section: Temperature-programmed Desorption (Tpd) Of O 2 and Cosupporting
confidence: 93%
“…The O1s spectra of the samples are deconvoluted and analyzed in detail by assuming that a single oxygen peak has a FWHM of 1.8–2.0 eV and with 80 % Gaussian plus 20 % Lorentzian peak shape . Considering the results in Figure S3, the contribution from carbonate has been excluded in the deconvolution and quantification.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, CO 2 ‐TPD experiments have been carried out to characterize the surface alkalinity of the catalysts (Figure a). It is reported that not only the overall alkalinity, but also the number of surface alkaline sites can affect significantly the C 2 product selectivity and yield , , , . While all the alkaline sites can play the role to activate CH 4 molecules, the intermediate strength alkaline sites are especially important to improve the coupling product selectivity , , , …”
Section: Resultsmentioning
confidence: 99%
“…Some transition metal containing catalysts, including Li/MgO, Mn/TiO 2 , and Mn/Na 2 WO 4 /SiO 2 , had been investigated and shown to be active for OCM. It is widely accepted that Li content is a promising chemical promoter for many kinds of OCM process catalysts . Extensive evaluations of the catalysts have identified that Mn content with different valence states are responsible for the catalysis in OCM…”
Section: Introductionmentioning
confidence: 99%